2015
DOI: 10.3892/etm.2015.2571
|View full text |Cite
|
Sign up to set email alerts
|

Association between mobilization of circulating endothelial progenitor cells and time or degree of injury from angioplasty in patients with exertional angina: A prospective study

Abstract: The aim of the present study was to investigate the effect of coronary artery angioplasty on the recruitment of circulating endothelial progenitor cells (EPCs) in patients with angina pectoris. A total of 66 patients treated by coronary stenting were enrolled in the PCI group and 17 patients that underwent angiography alone were enrolled in the control group. The EPC count in the blood was measured by flow cytometry prior to and at 1, 3, 5, 7 and 24 h following angioplasty in the percutaneous coronary interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
1
14
0
1
Order By: Relevance
“…Genetic or environmental factors such as diabetes and smoking induce vascular injury to cause functional deficiency of the vascular endothelium; moreover, clinical treatment, including balloon expansion or a stenting process, can also provoke damage to the endothelium . This endothelial injury results in an excessive inflammatory response leading to vascular diseases, including acute myocardial infarction and aortic dissection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic or environmental factors such as diabetes and smoking induce vascular injury to cause functional deficiency of the vascular endothelium; moreover, clinical treatment, including balloon expansion or a stenting process, can also provoke damage to the endothelium . This endothelial injury results in an excessive inflammatory response leading to vascular diseases, including acute myocardial infarction and aortic dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic or environmental factors such as diabetes and smoking induce vascular injury to cause functional deficiency of the vascular endothelium; moreover, clinical treatment, including balloon expansion or a stenting process, can also provoke damage to the endothelium. 34 This endothelial injury results in an excessive inflammatory Previous reports have shown that activation of the survivalrelated PI3K/Akt signaling pathway and endothelial-specific eNOS/ NO system is closely associated with endothelial cell function and dysfunction. 35 Notably, Akt-mediated NO secretion was proven to inhibit caspase-3 activation and consequently prevent apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is minimally invasive and is still a very efficient way to combat arterial stenosis and occlusion. Acute changes in circulating cell populations were demonstrated in course of endovascular treatment [32]. Moreover, endovascular procedure is a unique opportunity to access and evaluate direct vicinity of atherosclerotic plaque in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…[17] More recently, Gao et al have found the same EPC kinetics than us during the first 24 h post-PCI for CD133+, CD34+, KDR+ cells. [18] They also described that EPC mobilisation is influenced by the degree of endothelial injury.…”
mentioning
confidence: 98%